2005
DOI: 10.1186/cc3807
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The major potential adverse effect of use of sulfonylurea agents (SUAs) is a hyperinsulinaemic state that causes hypoglycaemia. It may be observed during chronic therapeutic dosing, even with very low doses of a SUA, and especially in older patients. It may also result from accidental or intentional poisoning in both diabetic and nondiabetic patients. The traditional approach to SUA-induced hypoglycaemia includes administration of glucose, and glucagon or diazoxide in those who remain hypoglycaemic despite rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In this therapeutic approach, transient beneficial increases in serum glucose are offset by rebound hypoglycemia that can especially occur in patients taking medications affecting pancreatic KATP β -cell channels such as sulfonylureas. This is caused by the additional glucose further stimulating insulin release in patients with intact pancreatic function (e.g., nondiabetics or patient with type-2 noninsulin dependent diabetes) [33, 34]. Given the similarities in biological mechanism to sulfonylureas, it is reasonable to propose that this phenomenon of rebound hypoglycemia may occur with fluoroquinolones as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this therapeutic approach, transient beneficial increases in serum glucose are offset by rebound hypoglycemia that can especially occur in patients taking medications affecting pancreatic KATP β -cell channels such as sulfonylureas. This is caused by the additional glucose further stimulating insulin release in patients with intact pancreatic function (e.g., nondiabetics or patient with type-2 noninsulin dependent diabetes) [33, 34]. Given the similarities in biological mechanism to sulfonylureas, it is reasonable to propose that this phenomenon of rebound hypoglycemia may occur with fluoroquinolones as well.…”
Section: Discussionmentioning
confidence: 99%
“…Octreotide is a potent and long-acting synthetic analog of the inhibitory peptide hormone somatostatin [33]. Voltage-gated calcium channels on the pancreatic β -cell membrane are coupled to G-protein somatostatin-2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of glucose or glucagon in patients with sulphonylurea-induced hypoglycemia may be unsatisfied because these antidotal approaches are associated with further exacerbation of insulin release by glucose and glucagon, leading to only temporary beneficial effects and later RH. 82 , 83 Octreotide can be safely and effectively used in treatment of sulphonylurea-induced hypoglycemia in patients with congestive heart failure and renal failure by adhering to dosing guidelines and close monitoring. 84 , 85 …”
Section: Overviewmentioning
confidence: 99%
“…Patients have also been described with sulphonylurea induced HH who are refractory to treatment with boluses of dextrose but respond to octreotide. 189 Since the first reports, there have been numerous studies 190 217 describing treatment of sulphonylurea overdoses with octreotide. In virtually all the studies that reported the use of octreotide, there were no serious adverse effects.…”
Section: The Role Of Sst Analogues In Treatment Of Hhmentioning
confidence: 99%